Penerapan Konsep Pembelajaran Geometri Menggunakan Tabel Interaktif dengan Pendekatan PMRI Kelas 5 SD - Wafna Janata Ulya; Septina Berlian Nustradamus; Eka Yuliana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research contains the level of understanding that students have regarding the application of mathematics in everyday life, especially regarding geometric education, this journal is also based on the lack of understanding of the concept of realistic mathematical reasoning. This research uses qualitative research methods using data collection methods, namely observation, interviews and document analysis. This research involves students and class teachers with the aim of gaining an understanding of the application of mathematics in everyday life.